1999
DOI: 10.1063/1.123404
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton detection using visible light photon counter

Abstract: Visible light photon counters feature noise-free avalanche multiplication and narrow pulse height distribution for single photon detection events. Such a well-defined pulse height distribution for a single photon detection event, combined with the fact that the avalanche multiplication is confined to a small area of the whole detector, opens up the possibility for the simultaneous detection of two photons. In this letter, we investigated this capability using twin photons generated by parametric down conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
191
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(193 citation statements)
references
References 13 publications
2
191
0
Order By: Relevance
“…Conventional photon detectors (e. g., EG&G SPCM) cannot distinguish a single photon from two or more photons. Single photon detectors, which were recently demonstrated experimentally, can distinguish a single photon from two or more photons [16]. In the following, we investigate the influence of the quantum efficiency on the output states in modes 6 and 2, and show that Alice and Bob receive a mixture of |Φ (+) 62 and |0 6 |1 2V unless they use single photon detectors with a unit quantum efficiency.…”
Section: Purification Using Imperfect Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional photon detectors (e. g., EG&G SPCM) cannot distinguish a single photon from two or more photons. Single photon detectors, which were recently demonstrated experimentally, can distinguish a single photon from two or more photons [16]. In the following, we investigate the influence of the quantum efficiency on the output states in modes 6 and 2, and show that Alice and Bob receive a mixture of |Φ (+) 62 and |0 6 |1 2V unless they use single photon detectors with a unit quantum efficiency.…”
Section: Purification Using Imperfect Detectionmentioning
confidence: 99%
“…The conventional photon detectors (e. g., EG&G SPCM) typically have the dark count rates of order 100 s −1 , which gives the value of ν ∼10 −6 for the coincidence time ∼10 ns. The single photon detectors [16] have the dark count rates of order 10 4 s −1 , which gives the value of ν ∼10 −4 for the coincidence time ∼10 ns. In both cases the effect of dark counts is negligible.…”
Section: The Effect Of Dark Countsmentioning
confidence: 99%
“…In combination with parametric down-conversion sources, photon number detection can also be used for the generation and conditioning of photonic Fock states 10 , as well as more complex quantum light states 11 . Furthermore, many applications beyond pure quantum information processing, such as quantum imaging 12 , tomography 13,14 and interferometry 15 , have been suggested to require error-free photon number detection, and extensive efforts [16][17][18][19][20][21][22][23][24][25][26][27][28][29] have therefore been devoted to developing photon number resolving detectors.…”
mentioning
confidence: 99%
“…Currently, most of the approaches to photon number detection [16][17][18][19][20] require cryogenic cooling, and thus do not address the need for a practical and scalable number resolving detector. In contrast, avalanche photodiodes (APDs) are a mature technology for single-photon detection, which operate close to room temperature, can be fabricated using standard semiconductor processing techniques and are ideal for integration into solid state quantum information processors.…”
mentioning
confidence: 99%
“…The most widely used single photon detectors at telecommunication and visible light wavelengths include avalanche photodiodes and photomultiplier tubes. 2,3 Bolometers, superconductor nanowire detectors, 4 and single quantum dot detectors 5 can be used to extend the single photon detection to far-infrared range. It has also been shown that field-effect transistors 6,7 and resonant tunneling diodes 8,9 ͑RTD͒ containing a layer of self-assembled quantum dots ͑QDs͒ can detect single photons and their temperatures of operation is at least 77 K. 10,11 The detection of a single photon in QDs based RTD ͑QDRTD͒ devices results from a capture of a photohole in a single dot, which in turn modulates the resonant current through the device.…”
mentioning
confidence: 99%